Partial-thickness burn wounds healing by topical treatment: A randomized controlled comparison between silver sulfadiazine and centiderm - Saeidinia, Amin; Keihanian, Faeze; Lashkari, Ardalan Pasdaran; Lahiji, Hossein Ghavvami; Mobayyen, Mohammadreza; Heidarzade, Abtin; Golchai, Javad (Medicine (Baltimore), 2017)
Burns are common event and associated with a high incidence of death, disability, and high costs. Centella asiatica (L.) is a medicinal herb, commonly growing in humid areas in several tropical countries that improve wound healing. On the basis of previous studies, we compared the efficacy of Centiderm versus silver sulfadiazine (SSD) in partial thickness burning patients. Study population comprised burn victims referred to Velayat Burning Hospital at Rasht, Iran. The intervention group received Centiderm and control group SSD cream. Burn wounds were treated once daily at home. All of the wounds were evaluated till complete healing occurred and at the admission, days 3, 7, 14 objective signs; visual acuity score (VAS) and subjective signs were recorded. Re-epithelialization time and complete healing days were recorded. We used random fixed block for randomization. The randomization sequence was created using the computer. Patients and burning specialist physician were blinded. Seventy-five patients randomized into 2 groups; (40 patients: Centiderm group; 35 patients: SSD group). The mean age of them was 30.67 ± 9.91 years and 19 of them were male (31.7%). Thirty patients in Centiderm and 30 patients in SSD group were analyzed. All of objective and subjective signs and mean of re-epithelialization and complete healing were significantly better in Centiderm group rather than SSD group (P < 0.05). There was no infection in Centiderm group. We showed that use of Centiderm ointment not only improved the objective and subjective signs in less than 3 days, but also the re-epithelialization and complete healing rather than SSD without any infection in the subjects.